Epidemiology of Leprosy in Childhood: A Retrospective Study - Rusmawardiana; Fifa Argentina; Indri Widya Sari (HM Publisher, 2021)
Background: Children are the group most susceptible to Mycobacterium leprae infection. The proportion of new leprosy cases in children is indicator of successful leprosy elimination program from World Health Organization (WHO), so this study would like to know the epidemiology of pediatric leprosy at Dermatology and Venereology Polyclinic, Dr. Mohammad Hoesin Palembang. Methods: Retrospective study of all new cases of leprosy in children (0-17 years) who came to Dermatology and Venereology Polyclinic, Dr. Mohammad Hoesin Palembang from January 2017 to December 2020. Results: There were 10 pediatric patients (7.58%) from 132 new leprosy cases. Most cases (40%) were in the 15-17 age group. There are more male than female. Most types of leprosy are BL (60%) followed by TT (20%). Manifestations of hyperpigmented skin patches and nervous disorders, grade 1 disability, and type 2 leprosy reactions are mostly found in type BL leprosy. The duration of illness 6-12 months has a grade 1 disability (30%). The history of positive contact came from same household in 3 cases (30%) with 7 people (70%) domiciled in Palembang. All cases received Multidrug Therapy (MDT) treatment according to WHO guidelines. Conclusion: Found 10 new cases of leprosy in children in Dermatology and Venereology Polyclinic Dr. Moh. Hoesin Palembang for four years, especially in the 15-17 age group, with the most cases being type BL leprosy. Household contact still plays an important role in leprosy transmission.